Toward zero discharge : (J. Wiley, 2005)
This book discusses pathways to achieve pollution prevention and waste minimization at the sources leading toward zero discharge. Coverage includes life cycle assessment, industrial ecology, eco-industrial parks, green engineering, and sustainable chemical and allied processes and products development. The pulp and paper industry is introduced as a case study in demonstrating how this industry is achieving pollution prevention goals by various techniques, and how this industry has become a minimum impact industry, moving towards achieving zero discharge status in most process areas